Pray for silence [compact disc, unabridged] - Castillo, Linda (Castillo, Linda. Kate Burkholder novel., 2010)
Police Chief Kate Burkholder has little to go on when an Amish family of seven is found murdered in their farmhouse. Marshalling her forces, Burkholder is determined to find the killer.